Understanding Mental Health and Spirituality. Issue 1 (17th July 2014) - Gilbert, Peter
Abstract : This chapter (Chapter 1, pp. 23–43) is reproduced in full from Spirituality and Mental Health © Pavilion Publishing & Media and Peter Gilbert, 2011, with permission of Pavilion Publishing and Media Ltd. The chapter was chosen as illustrative of Peter's inimitable style as well as of his key interests, many of which are discussed in John Swinton's tribute article, 'Peter Gilbert: In Memory of a Life Lived Well', in this issue of JSS .